2020
DOI: 10.3389/fphar.2019.01413
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Non-Alcoholic Fatty Liver and Cardiovascular Disease: Implications for Therapy?

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease worldwide. The most common cause of mortality in NAFLD is cardiovascular disease (CVD), and a key of focus in drug development is to discover therapies that target both liver injury and CVD risk. NAFLD and CVD are complex disease spectra with complex heritability patterns. Nevertheless, genome wide association studies and metaanalyses of these have identified genetic loci that are associated with increased risk of relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 85 publications
0
18
0
Order By: Relevance
“…52,53 Polygenic risk scores may predict the risk of NAFLD development and progression as well as cardiovascular disease. 52,[54][55][56][57] The Link between NAFLD and Risk of Cardiovascular Complications…”
Section: Pathophysiology Of Steatosismentioning
confidence: 99%
“…52,53 Polygenic risk scores may predict the risk of NAFLD development and progression as well as cardiovascular disease. 52,[54][55][56][57] The Link between NAFLD and Risk of Cardiovascular Complications…”
Section: Pathophysiology Of Steatosismentioning
confidence: 99%
“…The common rs641738C > T variant linked to the 3’ untranslated region of the MBOAT7 has been associated with a reduction in MBOAT7 intracellular hepatic expression at the mRNA and protein level. Moreover, down‐regulation of MBOAT7 regardless of genetic background is a maladaptive response to hyper‐insulinaemia promoting intracellular hepatic fat deposition as a result of impaired arachidonoyl‐phosphatidylinositol which leads to the conversion of saturated lysophosphatidylinositol to triglycerides, enhancing lipogenesis, 37,38 therefore, possibly increasing the risk of hepatic steatosis, NASH, hepatic fibrosis stage F2‐F4 and HCC without advanced fibrosis 39 . Figure 2 outlines a proposed model demonstrating potential effects of rs641738C > T near MBOAT7 on the liver in MAFLD.…”
Section: Effects Of Rs641738c > T Variant Near Membrane‐bound O‐acyltmentioning
confidence: 99%
“…NAFLD is a complex disease that is an intricate interplay of intertwined genetic and environmental factors [3][4][5]. On one hand, the Genome Wide Association Studies (GWAS) have identified variants in the genes PNPLA3, TM6SF2, GCKR, MBOAT7 and HSD17B13 that seem to be associated with susceptibility to and/or progression of NAFLD [6].…”
Section: Introductionmentioning
confidence: 99%